2020
DOI: 10.1093/qjmed/hcaa050.010
|View full text |Cite
|
Sign up to set email alerts
|

Sleeve gastrectomy with loop bipartition as a novel procedure for management of type 2 diabetes in obese patients

Abstract: Background Amidst the current worldwide epidemic of type 2 diabetes mellitus (T2DM), the global diabetes health burden is projected to reach 522 million in 2030, with much of this increase occurring in developing countries. Aim of the work to evaluate the role of laparoscopic sleeve gastrectomy with loop bipartition (single anastomosis sleeve ileal bypass) as a bariatric and metabolic procedure in control of type 2 diabetes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In the present study, HTN complete remission and improvement was observed in 75.8%, 80.7%, and 80.0% of hypertensive patients in the 1st, 2nd, and 3rd years after the surgery, respectively. The present findings were similar to previous studies, which were only conducted in the first [3, 10–13, 15–17] and second year after the surgery [18]. Also, according to the patients’ laboratory data and their feedback, HLD and OSA had 100% improvement in the present study, which is concordant the previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, HTN complete remission and improvement was observed in 75.8%, 80.7%, and 80.0% of hypertensive patients in the 1st, 2nd, and 3rd years after the surgery, respectively. The present findings were similar to previous studies, which were only conducted in the first [3, 10–13, 15–17] and second year after the surgery [18]. Also, according to the patients’ laboratory data and their feedback, HLD and OSA had 100% improvement in the present study, which is concordant the previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Results of 3-year follow-up of RYGB and SG showed efficacy in mean EWL, 45.0% and 39.2% and comorbidities resolution under 50% [9]. However, SASI permits a better weight control than RYGB and SG, and, the studies investigating the efficacy of SASI bypass were very promising at one year post-surgery [3,[10][11][12][13][14][15][16][17]. In patients undergoing SASI bypass in this study, EWL at 1 year was 87.3%, comparable to the 64-90% reported by previous studies [3,[10][11][12][13][14][15][16][17], and at 2 years was 90.7%, comparable to the 91.97% reported by Khalaf et al [18].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations